Flavonoids derived from licorice suppress LPS-induced acute lung injury in mice by inhibiting the cGAS-STING signaling pathway. (May 2023) - Wen, Jincai; Qin, Shuanglin; Li, Yurong; Zhang, Ping; Zhan, Xiaoyan; Fang, Mingxia; Shi, Ce; Mu, Wenqing; Kan, Wen; Zhao, Jia; Hui, Siwen; Hou, Manting; et al.
Abstract: In recent years, we have found that the dysregulation of the cyclic-GMP-AMP synthase (cGAS)‒stimulator of interferon genes (STING) pathway leads to the development of immune and inflammatory diseases, therefore, finding compounds that can specifically regulate this pathway is essential for effective regulation of the immune pathway for addressing inflammatory diseases. Licorice flavonoids (LFs), are active ingredients extracted from the Chinese herb licorice, which has been reported to have strong anti-inflammatory activity in previous studies. Here, we report that LFs inhibit the activation of the cGAS-STING pathway evidenced by the inhibition of the expression of type I interferons and related downstream genes such as interferon-stimulated gene 15 (ISG15) and C-X-C motif chemokine ligand 10 (CXCL10), as well as inflammatory cytokines such as interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α). Notably, LFs markedly improve the LPS-induced acute lung injury by inhibiting the excessive activation of cGAS-STING signaling pathway. Mechanistically, LFs treatment leads to the blocking of 2′3′-cyclic GMP-AMP (cGAMP) synthesis resulting in an inhibition of the activation of the cGAS-STING pathway. Our results indicate that LFs is a specific inhibitor of the cGAS-STING pathway, which is suggested to be a potential candidate for the treatment of cGAS-STING pathway-mediated inflammatory diseases. Graphical abstract: Image 1 Highlights: Licorice flavonoids in licorice can specifically inhibit the cGAS-STING signaling pathway. Licorice flavonoids inhibit the cGAS-STING pathway by reducing the synthesis of 2′3′-cGAMP. Licorice flavonoids have ameliorative effects on acute lung injury in mice.